Memory Deficits in Children with Mesial Temporal Sclerosis and Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers at Sao Paulo School of Medicine, Brazil, analyzed the occurrence of episodic memory (for personally experienced events) and semantic memory (for stored knowledge acquired in the past) deficits in 19 consecutive children with mesial temporal sclerosis (MTS) (8-16 years old; mean IQ 97).